Application of Vulcanization Process Simulation Technology in Rubber Elastic Element Research and Development - Jiling BU; Baibing LIU; Xi WU (机车电传动)
Aiming at the shortcomings in the traditional design methods of rubber elastic element molds and vulcanization process schemes, a vulcanization process simulation analysis technology and its application and achieved effects in the three elements of vulcanization and mold injection system design were introduced, which can be effective to reduce the costs of product trial and repair molds, shorten the R&D cycle, and save R&D costs